Systematic review and meta‐analysis of the early and late outcomes of open and endovascular repair of abdominal aortic aneurysm. Issue 7 (8th March 2013) - Stather, P. W.; Sidloff, D.; Dattani, N.; Choke, E.; Bown, M. J.; Sayers, R. D.
<x xml:space="preserve">Abstract</x> Background Any possible long‐term benefit from endovascular (EVAR) versus open surgical repair for abdominal aortic aneurysm (AAA) remains unproven. Long‐term data from the Open Versus Endovascular Repair (OVER) trial add to the debate regarding long‐term all‐cause and aneurysm‐related mortality. The aim of this study was to investigate 30‐day and long‐term mortality, reintervention, rupture and morbidity after EVAR and open repair for AAA in a systematic review. Methods Standard PRISMA guidelines were followed. Random‐effects Mantel–Haenszel meta‐analysis was performed to evaluate mortality and morbidity outcomes. Results The existing published randomized trials, together with information from Medicare and SwedVasc databases, were included in a meta‐analysis. This included 25 078 patients undergoing EVAR and 27 142 undergoing open repair for AAA. Patients who had EVAR had a significantly lower 30‐day or in‐hospital mortality rate (1·3 per cent versus 4·7 per cent for open repair; odds ratio (OR) 0·36, 95 per cent confidence interval 0·21 to 0·61; P < 0·001). By 2‐year follow‐up there was no difference in all‐cause mortality (14·3 versus 15·2 per cent; OR 0·87, 0·72 to 1·06; P = 0·17), which was maintained after at least 4 years of follow‐up (34·7 versus 33·8 per cent; OR 1·11, 0·91 to 1·35; P = 0·30). There was no significant difference in aneurysm‐related mortality by 2 years or longer follow‐up. A significantly higher proportion of patients undergoing EVAR required reintervention (P = 0·003) and suffered aneurysm rupture (P < 0·001). Conclusion There is no long‐term survival benefit for patients who have EVAR compared with open repair for AAA. There are also significantly higher risks of reintervention and aneurysm rupture after EVAR.